BER performance study of orthogonal frequency division multiplexing (OFDM) - Osman, Anis Salwa (2006)
A mobile radio channel is characterized by a multipath fading environment. The signal is offered to the receiver contains not only line of sight of radio wave, but also a large number of reflected radio waves that arrive at the receiver at different times. Delayed signals are a result of reflections from terrain features such as trees, hills, mountains, vehicles or building. These reflected delayed waves interfere with the direct wave and cause intersymbol interference (ISI), which causes significant degradation of the network performance. In order to overcome a multipath fading environment and achieve a wireless broadband multimedia communication system (WBMCS), it is possible to use OFDM transmission scheme. OFDM is based on parallel data transmission scheme that reduces that effects of multipath fading and renders complex equalizers unnecessary. OFDM is expected to be used in wireless LAN (WLAN) systems. In this project will study and identify t h e Orthogonal Frequency Division Multiplexing (OFDM) technology that gives the best BER performance in a multipath fading environment using computer simulation. Essentially, ideal and worst case communication channel models were studied and the simulation programs were written to simulate that channels. Orthogonal Frequency Division Multiplexing is modeled and simulated under different channel conditions such as AWGN and Rayleigh fading. Subsequently, a comparison study is carried out to obtain the BER performance for Orthogonal Frequency Division Multiplexing under under 1-path multipath fading conditions and to identify which channel gives the best BER performance. The comparison study showed that BER for AWGN channel gives the best BER performance compared to Rayleigh channel